Efektivitas Website Pesona Dukcapil dalam Pelayanan Online Administrasi Kependudukan : Perspektif Masyarakat dan Operator di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bangka - Eka Yuliani; Erni Yusnita; Ega Mawarni; Devi Valeriani (STIKes Ibnu Sina Ajibarang, 2024)
This study evaluates the effectiveness of the Pesona Dukcapil website as an online civil administration service in Bangka Regency from both public and operator perspectives. The research employed a qualitative descriptive method involving observation, interviews, and open-ended questionnaires. Findings indicate that most residents find the website helpful in terms of accessibility, service speed, information completeness, and service quality. Despite internet access challenges in some areas, overall user satisfaction remains high. From the operator's perspective, the website facilitates document management, improves productivity, and offers strong technical support. In conclusion, Pesona Dukcapil has proven effective in facilitating civil administration in the digital era and can serve as a model for efficient public service development.